The Relationships of Sexual Identity, Hazardous Drinking, and Drinking Expectancies With Risky Sexual Behaviors in a Community Sample of Lesbian and Bisexual Women. (September 2013) - Matthews, Alicia K.; Cho, Young Ik; Hughes, Tonda; Wilsnack, Sharon C.; Johnson, Timothy; Martin, Kelly
This study examined the influence of demographic characteristics, sexual identity, hazardous drinking, and sexuality/intimacy enhancement alcohol expectancies on rates of risky sexual behaviors in a community sample of women who self-identified as lesbian, mostly lesbian, and bisexual ( N = 349). Structured interview data were collected as part of a larger longitudinal study of sexual minority women's health, the Chicago Health and Life Experiences of Women study. We used structural equation modeling, controlling for demographic characteristics, to evaluate the influence of sexual identity, hazardous drinking, and alcohol-related sexuality/intimacy enhancement expectancies on sexual risk behaviors. Controlling for demographic characteristics and for sexual identity, higher levels of both hazardous drinking and sexuality/intimacy enhancement alcohol expectancies were associated with higher sexual risk scores. The final model predicted 36% of the variance in risky sexual behavior scores. Our findings regarding the central role of alcohol use and sexuality/intimacy enhancement expectancies in sexual risk behaviors among sexual minority women are consistent with previous research focusing on predominantly heterosexual women. Future efforts at sexual risk reduction in sexual minority women will need to address the influences of alcohol use and drinking-related expectancies on sexual behaviors and decision making.